2008
DOI: 10.1007/s10620-008-0301-3
|View full text |Cite
|
Sign up to set email alerts
|

A Glass of Water Immediately Increases Gastric pH in Healthy Subjects

Abstract: Water and antacid immediately increased gastric pH, while PPIs showed a delayed but prolonged effect compared to ranitidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Water can provide immediate symptom relief of heartburn; therefore, the ingestion of water during the intake of randomized study medication (suspension and capsule) may have affected the patients’ heartburn severity scores as well as the perceived speed of onset for each medication. One study demonstrated that a glass of water (200mL) increased gastric pH >4 in 10/12 healthy subjects after 1 minute, whereas the median time to pH >4 was 171 minutes for omeprazole[ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Water can provide immediate symptom relief of heartburn; therefore, the ingestion of water during the intake of randomized study medication (suspension and capsule) may have affected the patients’ heartburn severity scores as well as the perceived speed of onset for each medication. One study demonstrated that a glass of water (200mL) increased gastric pH >4 in 10/12 healthy subjects after 1 minute, whereas the median time to pH >4 was 171 minutes for omeprazole[ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 This could be due to gastric absorption of dissolved ibuprofen, as has been demonstrated in rats with a ligated pylorus, 61 or because of faster gastric emptying of the solution, 62 as initial emptying of water from the stomach is faster than that of radiolabeled gelatin or HPMC capsules of ibuprofen, 63 which in turn leads to faster absorption. 64 Further, it is possible that the gastric pH is temporarily elevated because of the salt dissolution as well as to the coadministration of water, 65 and thus accelerates the gastric emptying. 66 As Simcyp Simulator R in the current version does not account for gastric absorption and assumes GET is the same for solutions, solutions with precipitation and immediate-release solid dosage forms (assuming immediate disintegration of the dosage form into fine particles), it was to be expected that no sensitivity to gastric solubility would be detected in the sensitivity analysis.…”
Section: Sensitivity Analysis: Gastric Solubility and Getmentioning
confidence: 99%
“…In contrast, the short-term, temporary gastric acid reflux is mainly attributed to the mild GERD transient heartburn. Water and H2RAs increase the intragastric pH immediately, whereas PPIs increase it slowly [22]. However, PPIs have a more prolonged effect than H2RAs [3].…”
Section: Discussionmentioning
confidence: 99%